Pendidikan Nilai-Nilai Multikutural Dalam Al-Qur’an Surat Ar-Rum Ayat 22 Dan Al-Hujurat Ayat 13 - Abdillah, Syaik; Ismail, Faris (STAI Al-Musaddadiyah Garut, 2023)
The diversity of society necessitates the establishment of conditions where its elements act tolerantly, respect, and value each other's differences with an equal stance. Failing to do so may lead to frictions, conflicts, and social disintegration. Currently, the collective mindset regarding multicultural national values is often dominated by a logos-centric and hegemonic perspective, rife with prejudice, suspicion, hatred, and reductionism towards those outside their own group. Consequently, social bonds through collectivity and cooperation are confined within the group itself, excluding others. This research aims to address the following primary issues: (1) To identify the multicultural values within the Qur'an, and (2) To understand the concept of multicultural education as depicted in the Qur'an. The study adopts a library research approach utilizing a comparative analytical method. This method is employed to analyze the multicultural values and compare the interpretations of various Islamic scholars regarding Qur'anic verses on multiculturalism. The findings of this research indicate that multicultural education is a learning approach that recognizes and embraces diversity, differences, and plurality in terms of race, culture, and language. It also represents an effort to build and create an educational environment that ensures equality for all students, serving as a movement towards educational reform. Keywords: Multicultural Values, Qur'an, Surah Ar-Rum: 22, Al-Hujurat: 13